Dinamika Penyintas Menjadi Relawan: Studi Kasus pada Organisasi MDMC dalam Menangani Bencana Gempa, Tsunami dan Likuefaksi di Kota Palu - Indah Ahdiah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
This study aims to determine the background and motivating factors for survivors to become local volunteers in the earthquake, tsunami and liquefaction natural disasters that occurred on September 28 in the city of Palu. The method used is a qualitative method with a case study approach. The results of the study showed that being a survivor's background in volunteering was a position as a board or member of Muhammadiyah, and there was also an interest in MDMC work. The driving factors (1) imply the meaning of Al Maun, be useful human beings, (2) as an act of gratitude, (3) an expression of gratitude for the opportunity of life given by God, (4) working as a volunteer becomes one of the ways to restore emotions.